A chiroptical chemodosimeter for fast and specific detection of mercury(ii) ions in aqueous media. Issue 20 (18th September 2015) - Du, Ganhong; Liu, Keyuan; Liu, Beibei; Ye, Long; Jiang, Liming
Abstract : A simple Hg 2+ -specific CD probe has been developed taking advantage of an alkynyl ether oxymercuration mechanism for detection. Abstract : A simple salicylamide derivative, N -( o -propargyloxybenzoyl)-l -phenylglycinol, was designed and synthesized as a reactive probe for the detection of mercury ions. The chemodosimeter not only shows a fast and specific CD response to Hg 2+ ions in aqueous media but also has good compatibility with some potential organic species including cysteine and the oxidant N -chlorosuccinimide (NCS). The proposed chiroptical method may provide a useful alternative to chemosensors for detecting heavy-metal ions, which would cause luminescence quenching in chemosensor systems.